2019
DOI: 10.17645/pag.v7i4.2057
|View full text |Cite
|
Sign up to set email alerts
|

Food Democracy for All? Developing a Food Hub in the Context of Socio-Economic Deprivation

Abstract: This article proposes a localised and differentiated understanding of food democracy, or rather a plurality of localised food democracies. Based on the experiences of developing a local food hub in an area of socio-economic deprivation in the UK using a participatory action research (PAR) approach, it presents local responses to three key challenges derived from the literature. It argues that for civic food networks (CFNs) to contribute to a transition towards a food democracy, they need to address challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…The concept of justice is similar to fairness, which is associated with many alternative food networks and supply chains such as Fairtrade [245,246]. Other scholars addressed the concepts of "food democracy" [261,262,268,[270][271][272][273][274][275][276] or "food sovereignty" [261,[277][278][279][280][281][282][283], which are strongly linked to the way the food system is governed and managed and the inclusion of the different concerned stakeholders in the process of decision making about the future of agri-food systems, especially at the local level. Food democracy is a process that puts people at the center of and gives them a voice in and control over the transition towards more sustainable agri-food systems [270,271].…”
Section: Society and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The concept of justice is similar to fairness, which is associated with many alternative food networks and supply chains such as Fairtrade [245,246]. Other scholars addressed the concepts of "food democracy" [261,262,268,[270][271][272][273][274][275][276] or "food sovereignty" [261,[277][278][279][280][281][282][283], which are strongly linked to the way the food system is governed and managed and the inclusion of the different concerned stakeholders in the process of decision making about the future of agri-food systems, especially at the local level. Food democracy is a process that puts people at the center of and gives them a voice in and control over the transition towards more sustainable agri-food systems [270,271].…”
Section: Society and Culturementioning
confidence: 99%
“…These multi-stakeholder groups include food (policy) councils [274,368,[377][378][379][380][381][382], networks [281,344,383], and partnerships [384,385]. The innovative governance mechanisms allow increasing the participation and inclusion of stakeholders in managing food systems, thus democratizing it [261,262,268,[270][271][272][273][274][275][276]. In this regard, BĂ©nĂ© et al [386] suggested that "To operationalize the great food system transformation and ensure its sustainability, five areas of research and action require more attention: economic and structural costs; political economy; diversity of cultural norms; equity and social justice; and governance and decision support tools".…”
Section: Policy and Governancementioning
confidence: 99%
“…Not only do network connections foment social integration, but they also create empowerment through the collective sharing of knowledges and individual learning. Gardeners learn new skills, farmers learn to engage their community, volunteers learn to organize, and a broader sense of resources available in the local community is brought to the attention of all involved (Kingsley et al, 2019;Liu, Gilchrist, Taylor, & Ravenscroft, 2017;Prost, 2019;Trauger, Sachs, Barbercheck, Brasier, & Kiernan, 2010). Farmers who engage in civic agriculture are dependent on mutual education with consumers to demonstrate the importance of their craft and receive feedback on their work.…”
Section: Cultivating Social Capitalmentioning
confidence: 99%
“…The agricultural system describes a movement based on education, research, and socialization oriented towards building mutual awareness in realizing environmental balance, such as agricultural, conservation, and nature activities carried out through an agroecological approach (Ajates, 2020). As part of a collective movement, the social movement in this context involves many actors, including farmers, environmental activists, authors, the government, and the private sector (Prost et al, 2019).…”
Section: Conceptual Model Of Farmers' Social Movement Studymentioning
confidence: 99%